The importance of viewshed in nest site selection of a ground-nesting shorebird - Sharon S. Dorsey; Daniel H. Catlin; Shannon J. Ritter; Christy N. Wails; Samantha G. Robinson; Katie W. Oliver; Henrietta A. Bellman; Sarah M. Karpanty; James D. Fraser (PLoS ONE, 2025)
Birds and their nests are vulnerable to predation during the breeding season. Many birds have evolved nest placement strategies that minimize risk such as concealing nests in vegetation, or nesting in inaccessible cavities or on cliffs. Some ground-nesting species choose open areas where vegetative concealment or physical protection is minimal. These species may benefit from the ability to visually detect predators approaching the nest, affording them more time to perform evasive or distracting behaviors. We studied the nesting behavior of piping plovers (Charadrius melodus) on Fire Island, New York from 2015–2020 to determine if the area visible from the nest (i.e., ‘viewshed’) affected nest site selection. We calculated viewsheds at nests and random points and evaluated nest site selection using logistic regression modelling. Piping plovers selected nest sites with a greater view of predators than would be expected if nest site selection was random relative to viewshed. The inclusion of viewshed improved the predictive ability of a previous nest site selection model that was based on habitat characteristics present on the landscape in 2015, but its influence weakened as ecological succession progressed. Topographic variation was the predominant visual obstruction source at plover nest sites compared to vegetation height. Viewshed may play a role in nest site selection in other ground-nesting birds, and thus is an important factor to consider in the development of habitat management strategies and in understanding the evolution of behavior.